Direct Growth of Unidirectional Graphene Nanoribbons on Vicinal Ge(001). Issue 2 (18th September 2019) - Li, Panlin; Wang, Tianbo; Yang, Yuekun; Wang, Yalan; Zhang, Miao; Xue, Zhongying; Di, Zengfeng
Abstract : Long, highly oriented, semiconducting graphene nanoribbons (GNRs) are fabricated by chemical vapor deposition (CVD) on Ge(001) substrate. However, these anisotropic nanoribbons are apt to randomly distribute on Ge surface, which hinders their scalable applications in high‐performance graphene electronic devices. In this work, it is proved that the alignment of GNRs is closely related to the miscut angle of vicinal Ge(001) substrate. By investigating the growth behaviors of the GNRs on vicinal Ge(001) substrates with 0°, 4°, 8°, and 12° miscut toward Ge[111], it can be found that GNRs tend to nucleate along the orientation perpendicular to the miscut direction with the increase of miscut angle, and unidirectional GNRs are successfully synthesized on 12° miscut Ge(001) surface. Moreover, the shape of GNRs is also tuned by the miscut angle, which undoubtedly affects the aspect ratio of these GNRs. These promising results demonstrate that synthesizing unidirectional GNRs by the proposed method may promote the application of graphene in future nanoelectronic devices. Abstract : Graphene nanoribbons (GNRs) with unidirectional alignment are successfully synthesized on 12° miscut Ge(001) substrate via chemical vapor deposition (CVD) method. The alignment of GNRs on vicinal Ge(001) surface is heavily dependent on the miscut angle, which also affects the shape and aspect ratio of these GNRs.